Return to play, performance, and value of National Basketball Association players following Achilles tendon rupture. Issue 3 (3rd July 2021) - Chauhan, Avinash; Stotts, Jeff; Ayeni, Olufemi R.; Khan, Moin
ABSTRACT: Background : Achilles tendon ruptures are devastating injuries for National Basketball Association (NBA) players: prior studies have demonstrated decreased performance following return-to-play, but none have evaluated the effect of injury on rate-adjusted contextual statistics to assess the true change in performance. Additionally, there exists a paucity of data on the independent impact on defensive performance following return. Hypothesis : Compared to both control-matched peers and preoperative careers, we hypothesize that player production based on rate-adjusted contextual statistics will significantly decline following Achilles tendon rupture. Study design : Retrospective Cohort Study Methods : Publicly available NBA injury data on Achilles tendon rupture were reviewed from the 1996 –1997 to the 2016–2017 seasons. Controls were matched based on height, position, age, and rate-adjusted statistics. Extracted data included Value over Replacement Player Rating, Box Plus–Minus, Win Shares, offensive rating, defensive rating, and time to return-to-play, and was collected for the season before and two seasons following injury. Results : Twenty-five NBA players with surgically treated complete Achilles ruptures met inclusion and exclusion criteria. The return-to-play rate from Achilles tendon ruptures from 1996–1997 to 2016–2017 was 80%, with a mean recovery period of 311.0 ± 100.9 days. After 2 years, performance significantly declined for Value over Replacement Player Rating, Box Plus–Minus, and offensive rating compared to controls and cases. However, there was no significant effect on defensive rating ( P = 0.38). After two seasons, returning players had a Value over Replacement Player Rating that was 24.1% below pre-injury levels, contributed 1.4 fewer points per 100 possessions by Box Plus–Minus, and yielded 2.4 fewer wins by Win Shares. Conclusions : Achilles tendon rupture results in significant decreases in offensive production and career longevity. The injury does not have a significant impact on defensive production. Clinical relevance : Achilles tendon ruptures significantly affect basketball players ability to return-to-play, and their in-game performance. Level of evidence : 3